Growth performance of photoperiod-sensitive rice (Oryza sativa L.) varieties in different soil types under rainfed condition in Cambodia - Uch, Chanthol; Roeurn, Siranet; Ro, Sophoanrith; Kano-Nakata, Mana; Yamauchi, Akira; Ehara, Hiroshi (MDPI, 2023)
In Cambodia, rice is predominantly produced in areas with rainfed lowland conditions where photoperiod-sensitive varieties are cultivated. A number of varieties have been released for rainfed lowland areas, and the rice grain yield has reportedly increased by approximately 12% over the past ten years. Moreover, great fluctuations in yield performance have been observed across different soil types of the rainfed ecosystems of Cambodia. Therefore, the present study aimed to analyze the grain yield and stability among ten popular varieties that were released for rainfed lowland ecosystems across the four different soil types in Cambodia in two years. The grain yield varied 566 g m−2 as the highest in clay soil and about 220 g m−2 as the lowest in sandy soil. A combined ANOVA revealed significant differences for the main effect of genotype, environment, and genotype-by-environment interaction (GEI) for all yield-related traits and grain yield per square meter. The principal component test results showed that the heterogeneity of grain yield was mainly attributable to the effect of environment, followed by the effect of genotype. In fertile conditions, a higher percentage of filled grains was supported by higher leaf N until the late stage with a wider flag leaf. In conditions of moderate fertility, larger numbers of panicles were supported by a higher percentage of productive culms with higher leaf N until the late stage. In conditions of poor fertility, a higher percentage of filled grains was supported by higher leaf N until the late stage, which is considered to be important for higher grain yield. The variety Phka Rumduol showed these preferable traits and produced higher yields in fertile to poor natural soil fertility conditions with moderate variation. This variety is considered to be more desirable and ideal due to its stability and higher grain yield. The other varieties, namely, Phka Mealdei, Phka Rumdeng, and CAR4, were identified as above-average yielders. Therefore, those varieties potentially may be recommended for cultivation in rainfed lowland rice ecosystems in Cambodia due to their high yields. CAR4 showed moderate variation at the same level as Phka Rumduol. From the point of stability, Phka Rumduol and CAR4 can be expected to excel.